2013
DOI: 10.1016/j.biortech.2012.12.135
|View full text |Cite
|
Sign up to set email alerts
|

Ethanogenic fermentation of co-cultures of Candida shehatae HM 52.2 and Saccharomyces cerevisiae ICV D254 in synthetic medium and rice hull hydrolysate

Abstract: The ability of Candida shehatae, Saccharomyces cerevisiae, or the combination of these two yeasts in converting the mixed sugar composition of rice hull hydrolysate (RHH) as substrate for ethanol production is presented. In shake flask experiments, co-cultures showed ethanol yields (YP/S) of 0.42 and 0.51 in synthetic medium simulating the sugar composition of RHH and in RHH, respectively, with both glucose and xylose being completely depleted, while pure cultures of C. shehatae produced slightly lower ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 32 publications
1
25
0
4
Order By: Relevance
“…However, they exhibit some problems to assimilate pentoses carbohydrates [3]. Moreover, it has been reported that microorganisms that assimilate pentoses show low tolerance to inhibitors and require a small and well-controlled supply of oxygen to enhance alcohol production [3,4], therefore research of wild microorganisms adapted to specific substrates is still considered and attractive alternative to pentoses fermentation, since the knowledge of the strains behavior could be useful for future strategies and for its improvement. Yeasts of the genus Candida sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they exhibit some problems to assimilate pentoses carbohydrates [3]. Moreover, it has been reported that microorganisms that assimilate pentoses show low tolerance to inhibitors and require a small and well-controlled supply of oxygen to enhance alcohol production [3,4], therefore research of wild microorganisms adapted to specific substrates is still considered and attractive alternative to pentoses fermentation, since the knowledge of the strains behavior could be useful for future strategies and for its improvement. Yeasts of the genus Candida sp.…”
Section: Introductionmentioning
confidence: 99%
“…Co-culture fermentations may result in increased yield, improved control of product qualities, possibility of utilizing cheaper substrates and potential of improving existing processes [8]. These methods have been described to improve the efficiency of lignocellulosic biomass fermentation, having a great impact on the development of biofuels, bioenergy and biobased products [4,8,9]. On the other hand, carbohydrates concentrations of agroindustrial residues vary depending on the crop used and cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Co-culture of S. cerevisiae and other microorganism increases ethanol productivity which might be due to enhanced substrate utilization (Tesfaw and Assefa, 2014). Co-culture of S. cerevisiae with other microbes reduces inhibitory compounds in lignocellulosic hydrolysates (Tom´as et al, 2013;Taherzadeh and Karimi, 2011;Wan et al, 2012) which increases ethanol yield and production rate (Singh et al, 2014;Wan, 2012), shortens fermentation time, and reduces process cost (Hickert et al, 2013;Tesfaw and Assefa, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Outra alternativa para a produção de etanol a partir de pentoses é o emprego de micro-organismos recombinantes, os quais vêm sendo muito estudados (ELIASSON et al, 2000;DAVIS et al, 2005 ROBERTO et al, 1991;HAHN-HAGERDAL et al, 1994;NIGAM, 2001b;2002;CHANDEL et al, 2007;FERREIRA;DUSSÁN; CADETE et al, 2012;LIN et al, 2012;SILVA et al, 2012;BELLIDO et al, 2013;HICKERT et al, 2013 (NIGAM et al, 1985), insetos habitantes de madeira (TOIVOLA et al, 1984;SUH et al, 2003), madeira em decomposição (TOIVOLA et al, 1984; CADETE et al, 2009) SLININGER et al, 1987). A via das fosfopentoses consiste de uma fase oxidativa que converte hexoses fosfato em pentoses fosfato, suprindo o NADPH necessário na via biossintética, e uma fase não-oxidativa, na qual as pentoses fosfato são convertidas em hexoses fosfato e trioses fosfato (JEFFRIES, 1983).…”
Section: Micro-organismos Produtores De Etanolunclassified
“…Scheffersomyces stipitis e Candida shehatae têm apresentado resultados promissores na conversão de xilose em etanol a partir de hidrolisados de biomassa lignocelulósica, por exemplo, hidrolisados de bagaço de cana-deaçúcar, palha de arroz, entre outros (ROBERTO et al, 1991;HAHN-HAGERDAL et al, 1994;NIGAM, 2001b;2002;CHANDEL et al, 2007;FERREIRA;DUSSÁN;CADETE et al, 2012;LIN et al, 2012;SILVA et al, 2012;BELLIDO et al, 2013;HICKERT et al, 2013). James (1997) (conclusão)…”
Section: Em Diversos Trabalhos Realizados Em Frascos Erlenmeyer As Lunclassified